THE IMPLEMENTATION OF THE PICTURE AND PICTURE COOPERATIVE LEARNING MODEL IN IMPROVING LEARNING OUTCOMES IN ENGLISH LESSONS FOR EIGHTH GRADE AT SMPN 1 MESJID RAYA: A LITERATURE STUDY - Marlina Marlina; Rahmattullah Rahmattullah; Zahraini Zahraini (International Conference on Education, Science, Technology and Health (ICONESTH), 2024)
This study explores the implementation of the Picture and Picture cooperative learning model and its effects on enhancing learning outcomes in English lessons for eighth-grade students at SMPN 1 Mesjid Raya. Cooperative learning has gained recognition as an effective pedagogical approach that encourages collaboration among students, fostering a more engaging and interactive learning environment. The Picture and Picture model, specifically, allows students to visualize and connect concepts through images, promoting deeper understanding and retention of the material being studied. This research employs a literature review methodology, analyzing various studies and theoretical frameworks related to cooperative learning and the Picture and Picture model. The findings indicate that the application of this model not only improves student engagement and motivation but also significantly enhances their academic performance in English. Moreover, recommendations for educators on implementing this model effectively in the classroom are provided, highlighting its potential to transform traditional teaching practices.